Pemikiran Teologi Pendidikan Kristiani dalam Perspektif Paulo Freire - Debi Silvia Dinata; Melan Melan; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study starts from the observation that Christian education is still often delivered in a one-way, top-down manner. As a result, learners are less actively engaged in understanding their faith and social lives. Paulo Freire’s ideas on critical education offer an approach that emphasizes dialogue, participation, and social change. This study aims to examine Christian educational theology through Freire’s perspective and to explore how his ideas can be applied in learning processes. A qualitative approach was used, employing library research methods—reading, note-taking, and analyzing written sources related to Freire’s thought and Christian educational theology. The findings indicate that Freire’s approach can shift education from teacher-centered to learner-centered. Learning becomes more dialogical, encouraging critical thinking and deeper understanding of reality. Christian education then focuses not only on knowledge of faith but also on character development and spiritual life. Consequently, Christian education should be developed to be more open, participatory, and dialogical through activities such as group discussions, open Q&A sessions, and faith reflection. This enables learners to grow in faith while developing stronger social awareness. Future research is recommended to study the direct application of Freire’s ideas in Christian educational institutions.